2015
DOI: 10.1186/s13256-015-0564-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolated fracture of the humeral trochlea: a case report and review of the literature

Abstract: IntroductionIsolated fracture of the trochlea is a rarely reported entity. To the best of our knowledge, only 15 cases have been published. We report the case of a patient with an isolated fracture of the trochlea and discuss through a literature review the underlying mechanisms and the clinical, radiological and therapeutic features of this lesion. This work will significantly advance our understanding of this particular fracture.Case presentationA 21-year-old Caucasian man received an elbow injury. An antero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Nakatani et al [5] suggested the role of varus stress with axial loading in isolated trochlear fracture. Thus, it was documented that varus stress displaces the compressive forces of the radio-humeral compartment in the ulnohumeral compartment [12]. Back to our case, the fracture occurred following an axial load while the elbow was in an extended position.…”
Section: Discussionmentioning
confidence: 51%
“…Nakatani et al [5] suggested the role of varus stress with axial loading in isolated trochlear fracture. Thus, it was documented that varus stress displaces the compressive forces of the radio-humeral compartment in the ulnohumeral compartment [12]. Back to our case, the fracture occurred following an axial load while the elbow was in an extended position.…”
Section: Discussionmentioning
confidence: 51%
“…As far as the diagnosis of isolated coronal fractures of the humeral trochlea is concerned, a CT scan is imperative as the anteroposterior radiographs can be interpreted as normal in most of the cases and the lateral radiographs may show a half moon shaped osteochondral fragment which may be difficult to differentiate from capitellar fractures 11. CT scan also rules out any associated bony injuries along with determining the size and displacement of fragments thereby guiding the surgical technique 15. Open reduction and internal fixation is the treatment of choice for displaced fracture 1,5,7,8,11 . A medial or anterior approach is most often used, as both the approaches provide good exposure of the fracture 11. A lateral approach often limits the amount of surgical exposure and should only be considered in case of associated fractures of capitellum 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The "double arc sign," a half-moon shaped, dissociated fragment from the capitellum, appearing on the lateral view Journal of Orthopaedic Surgery 27 (2) of the radiograph is useful for diagnosis. 6 This sign may not be present in all cases 4,10 ; thus, it cannot be the sole diagnostic criterion. Adjuvant three-dimensional CT can assist in determining fracture configuration and in preoperative planning.…”
Section: Discussionmentioning
confidence: 99%